A STUDY OF CORRELATION BETWEEN ENGLISH CLUB PARTICIPATION AND STUDENTS’ ENGLISH LEARNING ACHIEVEMENT AT SMA PLUS BUDI UTOMO MAKASSAR - Fadilah, Siti; Khalik , Muh. Fihris; Nurjannah , Sitti (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2025)
This study aims to determine the correlation between students’ participation in the English Club Extracurricular and their learning achievement. This research is a quantitative research with correlation method. The population of this study was students of class XI SMA Plus Budi Utomo Makassar with a sample of class XI who are selected by using purposive sampling technique for selecting the sample because the target sample taken was students who took part in the English Club. The research data was collected using two instruments; questionnaires and data documentation. The questionnaire used is an open-closed questionnaire with the document used is student learning outcomes. The questionnaire was distributed to the students who joined on English Club. Then the results was analyzed by calculating using the Spearman correlation analysis method using SPSS 26.00 software with a significance level, the authors get a significant correlation of 0.008. The result is 0.000 < 0.05. Because 0.000 is lower than 0.05 (0.000 < 0.05), it means that there is a correlation between the student's participation in tutoring and the student's English achievement variable. In addition, from the data analysis, it was found that the Pearson Correlation was 0.644, which means that the correlation is strong according to the interpretation table correlation. Based on the research results, the null hypothesis is rejected. This means that there is a significant correlation between student participation in English Club and student learning achievements.